İstanbul kadılığı 225 No.’ lu şer’ iyye sicilinin transkripsiyonu ve değerlendirilmesi - Şahin, Salih (My University, 2001)
İstanbul Kadılığına ait 225 numaralı kadı sicili çerçevesinde yaptığımız tez çalışması giriş ve üç ana bölümden oluştu. Girişte kadı sicillerinin önemi ve mahiyeti hakkında bilgi verdik. Söz konusu sicillerin Osmanlı tarihini, ilgili oldukları dönemin sosyal yaşantısını, yönetim anlayışını ortaya koyma açısından birinci derecede önemli kaynaklar olduğu üzerinde durduk. Çalışmamızın birici bölümünde, klasik dönem Osmanlı kent yönetimi ve kent kurumları hakkında kısa bir değerlendirme yaptık. O dönemde kentin en önde gelen yöneticisi konumunda olan kadı ve yardımcılarının yetki ve sorumlulukları hakkında bilgi verdik. Yine o dönemde kamu hizmetlerini ifa eden kurumlar olan vakıflar, esnaf örgütleri ve mahalle yönetiminin kent yaşamı konusunda üstlendikleri fonksiyonları inceledik. Bu bölümün ikinci kısmında modern belediyeciliğin doğuşunu gerektiren etkenleri aktararak, üzerinde çalıştığımız kadı sicilinin ait olduğu yıl olan 1870'li yıllara kadar belediyeciliğin gelişim sürecini

olarak vermeye çalıştık. Tezimizin ikinci bölümünde ise üzerinde çalıştığımız kadı sicilinin içerdiği belgeleri konularına göre; alacak-borç, aile, gedik, vakıf, vasi-kayyım, köle-cariye, muarazadan men davaları şeklinde sınıflandırıp, söz konusu belgeleri konumuz çerçevesinde değerlendirmeye gayret ettik. Aynı zamanda bu sicilin tanıtımını yaptık. Üçüncü bölümde sicilin tam çeviri metnini verdik. Sonuçta ise genel bir değerlendirme yaparak çalışmamızı bitirdik. SUMMARY My studies couducted within the fromework of the records of İstanbul magistrate, numbered 225, on judicial decrees, documents such as title-deeds, and the trade monopoly as the right to exclusive exercise of a trade (profeeion) in a particular area, are composed of three main sections. As an introduction, I have given some information about the importance and the nature of the records of the local magistrate. I concentrated more on the records in guestion to show that they are first rate important sources in that they represent the Ottoman Hıstory, the social life of the related are and its management mentality. İn the first section of my study, I made a brief evaluation of the classical Ottoman urban management end also urban ınstitutions. I tried to give some information about the powers and the responsibilities of the judges and their deputies who were then the most distinguished adminis trators of the city. I' ve studied the functions assumed of the organizations such as foundations, guilds, and the local adminitrations which performed the public services of the time. İn the second part of the first section, I' ve summaried the process of development of municipal affairs until the years 1870s to which the records of the local magistrate go back, and cited about the factors which entail the rise of the modern municipality. İn the second section, after the documents which the records of the local magistrate included in, were classified according to their subjects such as: claims-debts, families, foundations, guardions-administeres of estates, male slaves-female slaves, actions as to legal protection of redress on the occasion of disturbed possession, etc. I, than, evaluated them whithin the scope of my main subject. I also gade a full description of that records. In the thirt second I made the textual trasnlations of thees records. Finally, I have copleted my studies making a general evaluation of the repor.
Keywords: Mahalli İdareler; ŞER’İYYE SİCİLLERİ-İSTANBUL